Odpowiedź:
a)
(x - 2)/x(x - 1) = 0
założenie:
x(x - 1) ≠ 0
x ≠ 0 ∧ x ≠ 1
D: x ∈ R \ { 0 , 1 }
x - 2 = 0
x = 2
b)
2x/(x - 1)
założenie:
x - 1 ≠ 0
x ≠ 1
D: x ∈ R \ {1}
2x = 3(x - 1)
2x= 3x- 3
2x - 3x = - 3
-x = - 3
x = 3
c)
(x - 3)/(x² - 9) = 1
założenie :
x² - 9 ≠ 0
(x - 3)(x + 3) ≠ 0
x ≠ 3 ∧ x ≠ - 3
D; x∈ R \ { - 3 , 3 }
x - 3 = x² - 9
x - 3 = (x - 3)(x + 3) | : (x - 3)
1 = x + 3
x = 1 - 3 = - 2
d)
6/x = x+5
założenie:
x ≠ 0
D: x ∈ R \ {0}
6= x(x + 5) = x² + 5x
x² + 5x - 6 = 0
a = 1 , b = 5 , c = - 6
Δ = b² - 4ac = 5² - 4 * 1 * (- 6) = 25 + 24 = 49
√Δ = √49 = 7
x₁ = (- b - √Δ)/2a = ( - 5 - 7)/2 = - 12/2 = - 6
x₂ = ( - b + √Δ)/2a = (- 5 + 7)/2 = 2/2 = 1